Особливості динаміки маси тіла і серця щурів після впливу антигенів в антенатальному періоді - Лебединець, Олександра Миколаївна; Волошин, Микола Анатолійович; Резніченко, Юрій Григорович; Lebedinets, A. N .; Voloshin, N. A .; Reznichenko, Yu. G .; Лебединец, А. Н.; Волошин, Н. А.; Резниченко, Ю. Г. (My University, 2013)
The dynamics of body weight and heart weight in the rats of Wistar lineat the period from one to 60 daysof postnatal development after intrauterine administration of antigens by the method of N.A.Voloshin have been investigated. Disproportion in development of rat hearts in experiment with a significant reduction of its relative weight at the period from 7 to 60days of life on the background trend in early terms and significant from 14to 60 days of postnatal development overweight of experimental animals have been established. The detected changes do not depend on the nature of the antigen and point to the heart morphofunctional disorders after antenatal antigens exposure. Изучена динамика массы тела и массы сердца крыс линии Вистар в сроки с первых по 60 сутки постнатального развития после внутриутробного введения антигенов по методу Н. А. Волошина. Выявленa диспропорция развития сердца экспериментальных крыс с достоверным снижением его относительной массы с 7 по 60 сутки жизни на фоне тенденции в ранних сроках и достоверной с 14 по 60 сутки постнатального развития избыточной массы тела экспериментальных животных. Выявленные изменения не зависят от природы антигена и свидетельствуют о диспропорции формирования сердца после антенатального воздействия антигенов.
Dynamics of body weight and heart weight in rats aft er antigen influence at аntenatal period
Особенности динамики массы тела и сердца крыс после влияния антигенов в антенатальном периоде
Keywords: морфогенез серця; щури; маса тіла; антенатальний вплив антигенів